PENGGUNAAN PUPUK KCl DAN HORMAX PADA TANAMANKUNYIT PUTIH (Curcuma alba L) - Agus Wahyudi; Ernita Ernita; T Rosmawati (UIR Press, 2015)
The purposes of this research are to examine the effect of KCl and hormax on growth and production of curcuma alba interaction and individual treatment. The research was conducted at the experimental farm of Faculty of Agriculture Riau Islamic University Pekanbaru from June to Bovember 2014. The completely randomized design was used with 4 x 4 factorial and 3 threatments. The first factor was KCl dose with four treatments i.e., without KCl, 3.5 g/plant, 7.0 g/plant, and 10.5 g/plant. The second factor was hormax concentration with four treatments, namely 0 cc/l, 3 cc/l, 6 cc/l, and 9 cc/l of water. The observed parameters were plant height, number of leaf, number of shoot, rhizome weight, and dried remnant weight per plant. The results were analyzed statistically at the 95% of confident level. The KCl and hormax intereactions had no significant effect on observed paameters. KCl dose had a significant effect on all observed parameters with the best treatment of KCl with doses of 10.5 g/plant. Furthermore, hormax concentration had a significant effect on all observed parameters with the best concentration of 9 cc/l of water.